2015
DOI: 10.1002/cpp.1995
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Effectiveness of Memory Specificity Training in Depressed Outpatients: A Pilot Study

Abstract: This study suggests that MeST is feasible in an outpatient setting, that it increases autobiographical memory specificity and that it may decrease depressive symptoms. A randomized controlled trial is recommended to examine MeST and its effects on autobiographical memory specificity, depressive symptoms and depressive relapse more extensively. Copyright © 2015 John Wiley & Sons, Ltd. Key Practitioner Message: Research suggests that modification of rAMS can advance recovery and reduce the chance of developing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 24 publications
10
33
0
Order By: Relevance
“…As such, one might question the extent to which our sample corresponds with other groups of depressed participants. The mean BDI‐II score of our participants with depression was similar to that from other studies in this area involving depressed participants (Eigenhuis, Seldenrijk, van Schaik, Raes, & van Oppen, ; Neshat Doost et al ., ; Raes, Williams, et al ., ; Werner‐Seidler et al ., ) so it is unlikely that our sample is exceptionally severe. Nevertheless, future research could examine the contribution of these variables to the observed effects by comparing samples of depressed participants that are medication naïve or not, who do or do not possess comorbidities or between in‐ and out‐patients.…”
Section: Discussionsupporting
confidence: 86%
“…As such, one might question the extent to which our sample corresponds with other groups of depressed participants. The mean BDI‐II score of our participants with depression was similar to that from other studies in this area involving depressed participants (Eigenhuis, Seldenrijk, van Schaik, Raes, & van Oppen, ; Neshat Doost et al ., ; Raes, Williams, et al ., ; Werner‐Seidler et al ., ) so it is unlikely that our sample is exceptionally severe. Nevertheless, future research could examine the contribution of these variables to the observed effects by comparing samples of depressed participants that are medication naïve or not, who do or do not possess comorbidities or between in‐ and out‐patients.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, the observed improvements in memory specificity were significantly associated with improvements in problem-solving skills, cognitive avoidance, and rumination, all variables that are hypothesized to mediate the impact of memory specificity on the course of depression. A recent uncontrolled study found that MEST also resulted in increased specificity of memory retrieval in 32 depressed outpatients (Eigenhuis et al 2015).…”
Section: Implications Of Mental Imagery For Cognitive Behavioral Intementioning
confidence: 99%
“…The authors of these reviews reported that no studies have yet examined the impact of a memory‐therapeutic intervention among people with BD. One intervention, Memory Specificity Training (MeST) (Raes, Williams, et al, ), is regarded as a promising method for improving memory specificity and remediating related symptoms and processes in UD (Eigenhuis, Seldenrijk, Schaik, Raes, & Oppen, ; Raes, Williams, et al, ; Werner‐Seidler et al, ), PTSD (Maxwell et al, ), and Schizophrenia (Blairy et al, ; Ricarte, Hernández‐Viadel, Latorre, & Ros, ). A recent meta‐analysis confirms these effects (Barry et al, ) and concluded that MeST has also been found to improve other processes associated with rAMS, such as deficits in problem solving, future‐oriented thinking, and hopelessness.…”
Section: Introductionmentioning
confidence: 99%